Where/How/For What Purpose Is Christ Being Proclaimed Today: Rethinking Proclamation in the World of Peripheries - SimonMary Asese Aihiokhai (Religions, 2023)
The content of proclamation cannot go unqueried if the much-needed work of addressing the structures of marginalities that play out in Christianity is to be completed. This task is urgent in order to address the role of Christianity in contemporary societies. To think that the proclamation of Christ is itself neutral, is to refuse to address how the structures that Christianity creates decide the fate of many in the world. A close study of the peripheries that Christian ecclesial structures create reveals the emergence of a form of a decolonial response to the agenda inherent in the embrace of a hegemonic approach to proclamation that plays out at the center of Christianity, and Christianity’s ecclesial institutions. These peripheries are a reminder that the center itself is in need of reform to allow for all who experience erasures to become visible.